2018
DOI: 10.1039/c7dt03742b
|View full text |Cite
|
Sign up to set email alerts
|

Photocatalytic function of the B12 complex with the cyclometalated iridium(iii) complex as a photosensitizer under visible light irradiation

Abstract: A visible light induced three-component catalytic system with the cobalamin derivative (B) as a catalyst, the cyclometalated iridium(iii) complex (Irdfppy, Irppy, Irpbt and [Ir{dF(CF)ppy}(dtbpy)]PF) as a photosensitizer and triethanolamine as an electron source under N was developed. This catalytic system showed a much higher catalytic efficiency than the previous catalytic system using [Ru(ii)(bpy)]Cl as the photosensitizer for the dechlorination reaction of 1,1-bis(4-chlorophenyl)-2,2,2-trichloroethane (DDT)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 40 publications
0
13
0
Order By: Relevance
“…The cobalt complex, Co(III)(DO)(DOH)Br 2 (Chart S1a), which is a well‐known functional model compound of B 12 , showed only a 10 % yield of 1 a (entry 7 in Table ). Its low reactivity may be due to its low stability under aerobic conditions with light irradiation, while the robust B 12 complex showed a high efficiency during the reaction . Subsequently, the catalytic reaction was carried out using a solar simulator to show the application of sunlight for the reaction and 1 a was produced in 95 % yield (entry 8 in Table ).…”
Section: Methodsmentioning
confidence: 99%
“…The cobalt complex, Co(III)(DO)(DOH)Br 2 (Chart S1a), which is a well‐known functional model compound of B 12 , showed only a 10 % yield of 1 a (entry 7 in Table ). Its low reactivity may be due to its low stability under aerobic conditions with light irradiation, while the robust B 12 complex showed a high efficiency during the reaction . Subsequently, the catalytic reaction was carried out using a solar simulator to show the application of sunlight for the reaction and 1 a was produced in 95 % yield (entry 8 in Table ).…”
Section: Methodsmentioning
confidence: 99%
“…The heterogeneous and hybrid B 12 -TiO 2 catalyst has been employed in hydrogenation and reductive dimerization of styrenes, 72 dehalogenation and ring expansion reactions of alkyl bromides 73,74 and dechlorination of benzotrichloride. 75 Remarkably, under anaerobic conditions, B 12 -TiO 2 reacts with benzotrichloride to form the corresponding 1,2-dichlorostilbenes. On the other hand, when the reaction is carried out under aerobic conditions, methyl benzoate is obtained quantitatively.…”
Section: Synpacts Syn Lettmentioning
confidence: 99%
“…The conductive band electron of TiO 2 ( E red = −0.5 V vs NHE in neutral water) could reduce 1 to form Co(I) species upon irradiation with ultraviolet (UV) light. We also reported a visible-light-driven system with a molecular photosensitizer such as Ru(bpy) 3 2+ [ 39 40 102 103 ], cyclometalated iridium(III) complexes [ 104 ], and organic red dyes [ 105 107 ].…”
Section: Reviewmentioning
confidence: 99%
“…The recycled use of 1 and [Ru(bpy) 3 ]Cl 2 was also achieved using an ionic liquid as the reaction medium [ 103 ]. Recently, we have found that cyclometalated iridium(III) complexes such as Irdfppy [ 112 ] are superior to [Ru(bpy) 3 ]Cl 2 in terms of their photosensitization abilities in visible-light-driven B 12 catalytic systems ( Scheme 9 ) [ 104 ]. This was probably due to the gradual decomposition of [Ru(bpy) 3 ]Cl 2 under visible light irradiation.…”
Section: Reviewmentioning
confidence: 99%
See 1 more Smart Citation